Comprehensive Clinical and Laboratory Follow-up of a Female Patient With Ebola Virus Disease: Sierra Leone Ebola Virus Persistence Study. (26th February 2019) - Liu, William J; Sesay, Foday R; Coursier, Antoine; Knust, Barbara; Marrinan, Jaclyn E; Whitmer, Shannon; McDonald, Suzanna L R; Gaillard, Philippe; Liu, Yang; Su, Qiudong; Zhang, Yong; Crozier, Ian; et al.
Abstract: The clinical, virologic, and immunologic findings in a female Ebola virus disease patient are described. During the long-term follow-up, Ebola virus RNA was detectable in vaginal fluid before 36 days after symptom onset, with nearly an identical genome sequence as in acute phase blood. Ebola-specific T cells retained activation at 56 days after disease onset.